Meeting the challenges of higher education in India through Open Educational Resources: Policies, practices, and implications - Thakran, Archana; Sharma, Ramesh Chander (Education Policy Analysis Archives, 2016)
Over the past two decades, the education sector in India has undergone a substantial transformation. Recent advances in technology have provided access to high quality educational resources and information on the Internet. This article examines the role of open educational resources (OER) in addressing the challenges of higher education in India, which range from geographical disparities in access to education, to shortages of trained and qualified faculty. The authors examine and discuss several OER initiatives that are currently advancing India’s efforts to create strong institutional mechanisms to overcome the country’s educational challenges through a national strategic framework designed to improve access to quality higher education. The authors explore these initiatives designed to increase access to education through OER, as well as those designed to develop OER-related skills for educators. The article concludes with a discussion of the implications of these initiatives for the development of open educational practices in India.